Regulating internet child pornography in Malaysia / Hayati Hassan and Nur Dafikah Harun - Hassan, Hayati; Harun, Nur Dafikah (Faculty of Law, 2015)
Cases involving children sexual abuse is on the rise in Malaysia. It is bad enough for children to become victim of rape, prostitution and sexual abuse. They have all become actors in child pornography. The Internet has aggravated the danger children face and sexual abuse. Easy access to the Internet given levy to paedophiles to satisfy their gratification by watching child pornography. Sad to say, the children are at stake and the law is not comprehensive to accord protection specifically in Malaysia. Applying qualitative research method, this project explored; the comprehensiveness of the law in protecting children towards child pornography, how other countries like Canada and United Kingdom protect children from Internet Child Pornography and what should be the reformation proposed in Malaysia to succumb this problem. As the benchmark, the law of UK and Canada was scrutinized to suggest recommendations to improve the law in Malaysia.